2018
DOI: 10.1097/opx.0000000000001265
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Measures of Daytime Activity and Sleep Disturbance in Retinitis Pigmentosa

Abstract: We find nonemployment/student status and sleep disturbances appear to be related to reduced daytime activity levels in adults with central vision loss due to RP. These findings underscore the importance of developing and evaluating interventions to help RP patients maintain engagement in productive activities and improve their disturbed sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…High WASO on a given night was significantly as-sociated with physical activity counts the next day in breast cancer patients with sleep disorders at the intra-individual level (13). This association was also found in adults with retinitis pigmentosa patients (14) or cystic fibrosis (52). No other significant associations were observed with other physical activity characteristics (i.e., moderate to vigorous physical activity (31,32,38,42,47), physical activity counts (41,45,51,56), and light, moderate, vigorous physical activity (34).…”
Section: Sleep Measures Temporally Associated With Physical Activity mentioning
confidence: 60%
See 4 more Smart Citations
“…High WASO on a given night was significantly as-sociated with physical activity counts the next day in breast cancer patients with sleep disorders at the intra-individual level (13). This association was also found in adults with retinitis pigmentosa patients (14) or cystic fibrosis (52). No other significant associations were observed with other physical activity characteristics (i.e., moderate to vigorous physical activity (31,32,38,42,47), physical activity counts (41,45,51,56), and light, moderate, vigorous physical activity (34).…”
Section: Sleep Measures Temporally Associated With Physical Activity mentioning
confidence: 60%
“…Among the included studies, eight combined self-reported, and objective measures of sleep parameters (14,30,38,45,(53)(54)(55)(56). All measures are detailed in Table 1.…”
Section: Sleep and Physical Activity Measuresmentioning
confidence: 99%
See 3 more Smart Citations